Friendship and Love, Ethics and Politics : Studies in Mediaeval and Early Modern History - Österberg, Eva, 1942- (Book collections on Project MUSE., 2010)
Today, friendship, love and sexuality are mostly viewed as private, personal and informal relations. In the mediaeval and early modern period, just like in ancient times, this was different. The classical philosophy of friendship (Aristotle) included both friendship and love in the concept of philia. It was also linked to an argument about the virtues needed to become an excellent member of the city state. Thus, close relations were not only thought to be a matter of pleasant gatherings in privacy, but just as much a matter of ethics and politics. What, then, happened to the classical ideas of close relations when they were transmitted to philosophers, clerical and monastic thinkers, state officials or other people in the medieval and early modern period? To what extent did friendship transcend the distinctions between private and public that then existed? How were close relations shaped in practice? Did dialogues with close friends help to contribute to the process of subject-formation in the Renaissance and Enlightenment? To what degree did institutions of power or individual thinkers find it necessary to caution against friendship or love and sexuality? These are some of the questions raised in the book, on the basis of different European sources. The discussions touch upon changes in the distinctions between private and public, in subject-formation and legal practices, as well as the varying cultural, existential and ethical importance of close relations in history.